Reversible sensorineural hearing loss in a late presentation of acute disseminated encephalomyelitis: A case report - Laith Haddad; Simone Khalifeh; Nadia Koleilat; Mona Hnaini (Acta Oto-Laryngologica Case Reports)
Acute disseminated encephalomyelitis (ADEM) is a demyelinating disease of the central nervous system. It presents with a variety of symptoms including fever and encephalopathy. Hearing loss is a rare symptom. We present a 10-year-old girl who exhibited late-onset isolated hearing loss following an episode of ADEM that had not been treated. Initially, she displayed classical symptoms, but her hearing loss became the predominant concern weeks later, so intravenous corticosteroids were given. Remarkably, this treatment resulted in a significant partial reversal of her hearing ability. This highlights the potential for hearing loss as a late complication of ADEM. The improvement following corticosteroid therapy suggests that inflammation may play a critical role in the pathophysiology of auditory dysfunction. Our review of literature indicates a limited number of similar reports, underscoring the rarity and clinical significance of this symptom. This case adds valuable insight into the spectrum of ADEM and its atypical presentations.